2006
DOI: 10.1002/bdd.512
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on the pharmacokinetics of verapamil and norverapamil in human

Abstract: The effects of gender on the pharmacokinetics of verapamil and its active metabolite, norverapamil, following single oral dose (80 mg, Isoptin) to 12 healthy male (mean age: 25.75+/-2.42 years, mean body weight: 70.59+/-9.94 kg) and 12 healthy female subjects (mean age: 24.08+/-2.84 years, mean body weight: 56.67+/-5.23 kg) were investigated in the present study. Plasma concentrations of verapamil and norverapamil were analysed using a modified high-pressure liquid chromatography method. Pharmacokinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, in the study of pharmacokinetics, women had higher plasma concentrations of β‐blockers 119122 and possibly also of verapamil 123125 than men. The differences in concentrations seemed to be related to differences in activity of drug-metabolism pathways and gastrointestinal absorption.…”
Section: Pharmacological Mechanismsmentioning
confidence: 97%
“…However, in the study of pharmacokinetics, women had higher plasma concentrations of β‐blockers 119122 and possibly also of verapamil 123125 than men. The differences in concentrations seemed to be related to differences in activity of drug-metabolism pathways and gastrointestinal absorption.…”
Section: Pharmacological Mechanismsmentioning
confidence: 97%
“…Gender variability in the pharmacokinetics of drugs metabolized by different enzymatic pathways has been described [6,7]. Although differences in the activity of CYP3A4 between genders have been reported [8][9][10], pharmacokinetic differences in drugs metabolized by this enzymatic pathway are not always observed [11][12][13][14]. Due to this controversy, it is difficult to establish a priori if gender differences in the pharmacokinetics of drugs metabolized by CYP3A4 will be present.…”
Section: Introductionmentioning
confidence: 99%
“…In the sinoatrial (SA) and atrioventricular (AV) nodes of the heart, CCBs slow the Ca 2+ -dependent upstroke of the action potential, thereby reducing automaticity of the SA node and slowing impulse conduction through the AV node. Gender-related pharmacokinetic differences for several CCBs, including amlodipine and verapamil, have been described [68,69]. Women achieve higher plasma concentrations of amlodipine and display faster oral elimination rates for verapamil compared to men.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Women achieve higher plasma concentrations of amlodipine and display faster oral elimination rates for verapamil compared to men. This difference can be partially attributed to the lower body weight, higher activity of CYP3A4 and lower activity of P-gp in women compared to men [68,69]. An 18 week, open-labeled, prospective study demonstrated that amlodipine exerted a greater antihypertensive effect in women compared to hypertensive men across all age groups [70,71].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%